Knowledge and attitudes towards contraception among Polish women aged 45-54 years - Bińkowska, Małgorzata; Dębski, Romuald; Bednarowska-Flisiak, Alicja (Menopause Review/Przegląd Menopauzalny, 2004)
The objective of the study was to investigate awareness of contraception methods and attitudes towards contraception among women aged 45 to 54 years. The study included Polish nationwide representative randomised sample of 1083 women. The respondents evaluated themselves their awareness of various contraception methods and based on prepared answer options they evaluated acceptability, efficacy, comfort and safety of the use of different contraception methods. The women’s awareness of contraception seems insufficient and to considerable extent dependent on their education level and place of residence. However among women who declare high awareness of contraception these factors are loosing their importance. High awareness is associated with significantly more frequent acceptance of using contraception, higher evaluation of its efficacy, comfort and safety, especially in case of new forms of contraception. Women who use hormonal replacement therapy significantly more often accept the use of contraception pill and express positive opinions on its efficacy and safety.